Status of the role of Jordanian schools in confronting the moral crisis from the teacher's perspective - Al- shdefat, Muneera Abd Al- kareem (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the role of Jordanian schools in confronting the moral crisis from the point of view of teachers in Jordanian schools.The study population consisted of all the teachers in Jordanian schools of the Jordanian ministry of education for the academic year 2017/2018. The study sample consisted of (50) teachers who were selected as representatives of the study society. The study followed the method of qualitative research due to its relevance to the nature of the study and used the interview for this purpose.The results of the study showed that there is a role for the Jordanian schools in facing the moral crisis، which was clear and effective by the commitment of the schools to the teachings of the Islamic religion.The study recommended the need to highlight the ethical aspects in the curriculum and linking them to the Islamic faith and develop the role of the teacher in the development of the moral values of students.
Keywords: moral crisis; ethical